Dosimetry and Therapeutic Ratios for Rhenium-186 HEDP. (11th April 2013) - Argyrou, Maria; Valassi, Alexia; Andreou, Maria; Lyra, Maria
Abstract : Rhenium-186 (Re-186) is a β -emitting radionuclide. Emitted β -particles have ranges up to 4.5 mm in tissue, capable of delivering high doses to skeletal regions of high Re-186 concentrations while sparing adjacent radiosensitive regions and thus making the irradiation well tolerated for the patient. Along with the β -emissions, γ -rays are emitted having an adequate energy for imaging during therapy and biodistribution assessment for patient-specific dosimetry calculations. The relatively short physical half-life combined with the β -emissions allows the delivery of relatively high activity rate for a short period of time in areas of concentration. This study is a short review concerning the palliative treatment of skeletal metastases using 186 Re-HEDP. After presenting the dominant ways of 186 Re production, special emphasis is given to dosimetry issues while the effect of palliation therapy can be evaluated through the comparison of the absorbed dose in metastatic lesion relatively to the normal bone region. Accurate dose estimation is required taking into account the anatomic individual difference of each patient. For this purpose a patient specific dosimetric model considering metastatic lesions as spherical nodules is introduced. In order to quantify in a representative way the results of palliation treatment, the concept of therapeutic ratios is analyzed.